2021
DOI: 10.3390/pharmaceutics13020140
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Vaccination: Conventional Vaccine Approaches Versus New-Generation Strategies in Combination with Adjuvants

Abstract: The current COVID-19 pandemic, caused by severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2), has raised significant economic, social, and psychological concerns. The rapid spread of the virus, coupled with the absence of vaccines and antiviral treatments for SARS-CoV-2, has galvanized a major global endeavor to develop effective vaccines. Within a matter of just a few months of the initial outbreak, research teams worldwide, adopting a range of different strategies, embarked on a quest to develop eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 182 publications
(110 reference statements)
0
32
0
Order By: Relevance
“…Moreover, adjuvants can be added to the interior of the lipid nanoparticles for further upregulation of the immune system's response to the vaccine. Lipid nanoparticle-based technology can be a beneficial solution to challenge RNA delivery to cells [149][150][151][152][153][154][155][156]. Vaccine development by nanotechnology improves nucleic acid delivery and conformationstabilized subunit vaccines to lymph nodes.…”
Section: Mrna Vaccinementioning
confidence: 99%
“…Moreover, adjuvants can be added to the interior of the lipid nanoparticles for further upregulation of the immune system's response to the vaccine. Lipid nanoparticle-based technology can be a beneficial solution to challenge RNA delivery to cells [149][150][151][152][153][154][155][156]. Vaccine development by nanotechnology improves nucleic acid delivery and conformationstabilized subunit vaccines to lymph nodes.…”
Section: Mrna Vaccinementioning
confidence: 99%
“…Aluminum adjuvant was first used in clinical trials in the 1930s and is still used in approximately 80% of the vaccines that are delivered with adjuvants ( Bouazzaoui et al, 2021 ). Recently, it was reported that three doses of a dimeric RBD-based protein subunit vaccine adjuvanted with aluminum hydroxide were well-tolerated and immunogenic against COVID-19 in phase 1 and 2 trials ( Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) is a RNA airborne virus infection known as the pathogen responsible for coronavirus disease 2019 (COVID-19) [119]. Millions of COVID-19 patients have been reported thus far; however, there is no concrete evidence on the effectiveness and safety of the specific treatment against SARS-CoV-2 [120,121].…”
Section: Perspectives Anti-sars-cov-2 (Covid-19) Effectmentioning
confidence: 99%